当代中国政治话语中和 谐文化因子解读 = Interpretation on the Cultural Factors of Harmony in Contemporary Chinese Political Discourses (Sinología hispánica. China Studies Review, 2015)
当代中国政治话语建立在中国文化价值基础之上，通过“以人为本”、“和而不同”、“德法和谐”、“中国梦”等和谐话语体现出来。本研究力图从语言和文化的视角对上述和谐文化价值因子进行分析解读，探究其形成的历史文化渊源，挖掘其文化内涵，寻找其普世价值意义，从而进一步促进世界文化多样性的和谐构建。The contemporary Chinese politicaldiscourse, with Chinese cultural values as itsfoundation, demonstrates such discursive ideasas ‘people foremost’, ‘harmony within diversity’,‘co-existence between morals and law’,‘China’s Dream’, and so on and so forth. Thispaper makes an interpretation of theseharmonious cultural factors by exploring thehistorical origins as well as cultural connotation,trying to seek its universal values for furtherpromotion of the harmonious construction ofglobal cultural diversity.